Influence of ag content on mechanical and tribological behavior of DLC coatings - Manninen, N. K. (2013)
Ag–DLC coatings with Ag contents ranging from 1.3 at.% to 13.1 at.% were deposited by DC magnetron sputtering. The coatings were characterized with respect to their structure (by means of XRD and Raman spectroscopy), mechanical and tribological properties (by scratch test, nanoindentation, residual stress measurements and pin-on-disk test). The incorporation of 13.1 at.% Ag resulted in the formation of Ag grains of 2–3 nm which promoted the increase of graphite like bonds organized in rings. Regarding the mechanical properties, no variations were found for films with Ag contents lower than 13 at.%; a reduction of both hardness and compressive residual stress was then observed for higher values. Pin-on-disk tests were performed at two different contact pressures (690 MPa and 1180 MPa) in dry sliding conditions against a zirconia counterpart. For the lower contact pressure the variations in the wear rate are well correlated with the coating structure and mechanical properties, while for the higher contact pressure the presence of Ag is relevant and Ag–DLC coatings are showing higher wear rate than DLC one. SEM analysis revealed the formation of Ag aggregates on the wear track and adhesion of silver to the counterpart.